Drag and Lift Forces in Blunt and Aerodynamic Bodies: Drag and Lift Forces in Blunt and Aerodynamic Bodies - Flores Zhamungui, Milton; Baidal Bustamante, Eduardo; Varas Flores, Richard (EASI: Engineering and Applied Sciences in Industry, 2025)
The objective of this study is to analyze the drag and lift forces acting on blunt and streamlined bodies. To achieve this, experiments were conducted in a subsonic wind tunnel using objects of varying geometries, including a small smooth sphere, a large smooth sphere, a rough sphere, a flat disk, and a streamlined body — specifically, a NACA airfoil profile. Airflow within the tunnel was generated using a variable-speed fan, operated at different rotation speeds. Data collection was performed with the aid of specialized software, recording fifty measurements for each case, including drag force, kinematic viscosity, temperature, and airflow velocity. The results were used to construct plots of the drag coefficient versus Reynolds number for the blunt bodies, and the lift coefficient versus Reynolds number for the NACA airfoil, enabling a comparative analysis of aerodynamic behavior across different geometries.